Design and implementation of digital twin simulation system for hydraulic servomotor - Jiang, Zhanpeng; Tang, Jun; Sun, Yingbing; Liu, Zijian; Wu, Fenghe (International journal of advanced manufacturing technology, 2025)
The increasing complexity and performance demands of hydraulic servomotors necessitate advanced simulation techniques for their design and optimization. In this study, a digital twin simulation system for hydraulic servomotors was developed, integrating an embedded data acquisition front-end with a distributed real-time simulation system. This system integrates real-time data acquisition with high-fidelity virtual modeling to provide an accurate and dynamic representation of the servomotor’s behavior. Leveraging this high-fidelity simulation capability within the distributed architecture enables the identification and analysis of potential operational issues, thereby improving the reliability and performance of the hydraulic servomotor. The implementation of this digital twin simulation system effectively reduces control system development time, mitigates development risks, and addresses the drawbacks of high testing costs and system complexity. Experimental results demonstrate the proposed system’s effectiveness in simulating various fault scenarios, indicating its potential for widespread adoption in industrial applications.